Analisa Penerapan ERP dalam Meningkatkan Kinerja SCM Grand Pet Shop - Immanuel Zai; Yulfiswandi; Defen; Florensia Sutjiali; Nathania Jocelyn; Sherlyca Styvani; Vonnylia; Windy Wihue Tarekar (STEKOM PRESS, 2023)
The purpose of this study is to determine the application of company resource management and supply chain management at the Grand Pet Shop. In conducting an analysis of business partners, researchers used qualitative methods in the form of direct interview techniques with the owner of the Grand Pet Shop. The results found through analysis, Grand Pet Shop has implemented a supply chain process including planning, processing, storage, shipping and returns of goods then partners have also involved 4 functional areas, namely marketing and sales, supply chain management (SCM), accounting and finance, and human resources in running their business as well as analyzing the use of Enterprise Resource Planning (ERP) is still not recommended at this time because there has not been found a suitability for Grand Pet Shop use due to the high cost and the Enterprise Resource Planning system is too complicated for Grand Pet Shops which are still SMEs, but do not rule out the possibility in the future.